The Effects of Exercise on Appetite in Older Adults: A Systematic Review and Meta-Analysis - Hubner, Sarah; Boron, Julie Blaskewicz; Koehler, Karsten (Frontiers in Nutrition, 2021)
Background: The effect of physical activity and exercise on hunger and satiety has been well-studied in younger adults, but the influence of aging is less understood. While some evidence suggests that acute bouts of exercise induce a compensatory eating drive, long-term activity may improve satiety sensitivity. The objective of this study was to investigate the effects of exercise on appetite in older adults. Methods: We systematically reviewed available literature investigating the effect of exercise on appetite in older adults (Prospero, 2020, Blinded for Review). PubMed, PsycINFO, Academic Search Complete, the Sports Medicine & Education Index, and Web of Science, were searched for peer-reviewed articles published in English with no date restriction. Included studies implemented a primary exercise or physical activity intervention with a control group, on a generally healthy population ≥60 years of age. Selected studies included at least one appetite outcome. Risk of bias was assessed using the 11-point Physiotherapy Evidence Database (PEDro) tool. Standardized mean difference summary statistics (Hedge’s g effect sizes) and 95% confidence intervals were reported. Results: We identified 15 reports (13 studies) which met all inclusion criteria (5 resistance training, 3 aerobic, 6 mixed modalities). Studies included 443 participants (Age=68.9±5.2, 82.3% female) and had generally ‘good’ bias scores (PEDro=6.4±0.88). Random effects meta-analyses revealed that the exercising group showed statistically significant reductions in glucose [SMD = −0.34 (95% CI: −0.67, −0.02), p< 0.05, PEDro =6.4±0.45] and leptin [SMD = −0.92 (95% CI: −1.28, −0.57), p< 0.00001, PEDro =6.2±0.75]. Discussion: This systematic review revealed that exercise and physical activity may modulate resting hunger and satiety in older adults. Decreases in fasting leptin and glucose hormones suggest that exercise promotes satiety sensitivity in adults aged 60+. This review highlights that engaging in exercise and activity programs may provide a meaningful avenue for improving chronic and functional disease burden in later life by promoting appetite control and balanced energy intake. Recommendations for future research include investigations of appetite in response to varied exercise modalities within more diverse and representative samples of older adults.